A New Encounter with Lasia concinna and its beetle-trapping bloom - Sin Yeng, Wong; Alistair, Hay; Peter C., Boyce (International Aroid Society, 2020)
Lasia concinna is the second named species in a genus much better known by the extremely widespread L. spinosa (L.) Thwaites (India and Sri Lanka to New Guinea and the Bismarck Archipelago — Hay, 1988a), the prickliest of all aroids. It was for a long time known only from a plant cultivated in Java at the Kebun Raya, Bogor from which it was originally named by van Alderwerelt van Rosenburgh (1920). It had been collected on one of the (Dutch) Nieuwenhuis expeditions to Borneo at the end of the 19th Century, but no original herbarium material has been located, so it remains unknown from where it came exactly. It was first recorded in a Bogor gardens catalogue in 1916 (Hay, 1988), and exactly a century later the plant was dead (Yuzammi, 2018). However, the species was rediscovered in West Kalimantan, Indonesian Borneo, in 1996 (Hambali & Sizemore, 1997) in the Kapuas River valley, to which area it seems to be endemic and where we had the opportunity to visit in October 2019.